Light-assisted synthesis MoSx as a noble metal free cocatalyst formed heterojunction CdS/Co3O4 photocatalyst for visible light harvesting and spatial charge separation. Issue 20 (8th May 2018) - Yang, Hao; Jin, Zhiliang; Wang, Guorong; Liu, Duanduan; Fan, Kai
Abstract : In this paper, a novel photocatalyst with visible light harvesting and spatial charge separation is reported, in which cobalt oxide and molybdenum sulfide are assembled on the surface of cadmium sulfide nanorods. Abstract : In this paper, a novel photocatalyst with visible light harvesting and spatial charge separation is reported, in which cobalt oxide (acting as a hole trap) and molybdenum sulfide (acting as an electron trap) are assembled on the surface of cadmium sulfide nanorods. The MoS x /CdS/Co3 O4 composite photocatalyst shows a high H2 evolution with a yield of 537.51 μmol in 5 h, which is 35.53 times greater than over pristine CdS (15.13 μmol). The detailed underlying reason was comprehensively studied and understood by means of SEM, TEM, XRD, XPS, UV-vis DRS, BET; in particular, investigation of their photoelectrochemical properties with photocurrent, voltammetric scanning, fluorescence spectra etc . The high photocurrent response, the lower overpotential (−0.37 V vs. SCE), the faster electron transfer rate constant ( k et = 4.23 × 10 9 s −1 ) and the short fluorescence lifetime (0.457 ns) supported the efficient spatial charge transfer between CdS and MoS x as well as Co3 O4 . The simultaneous loading of bicocatalysts can significantly improve the photo-induced spatial charge separation of CdS because MoS x nanoparticles act as an electron trap to rapidly transfer electrons from CdS while Co3 O4 acts as a hole trap to quickly transfer holes, enhancing its photocatalytic performance as well.